Monsters Escaping the Screen: Embodied Narratives of LARPS and Zombie Walks - Stenström, Kristina (Kvinder, Køn & Forskning, 2017)
This article engages with communities that invite monstrous characters to come to life and invade three-dimensional spaces through real-life bodies. Through focus group interviews with participants in live action role-play (LARP) and zombie walks in Stockholm, this text explores the ways in which participants engage in physical encounters with monstrosity and the surrounding narrative worlds. First, I address how monstrous corporeality not only functions as fiction or escape but most concretely taps into contemporary discourses connected to corporeal change. Through Butler’s performativity and becoming and in connection with discourses of makeover culture, I argue that both LARPs and walks function as both performances and performative acts in which demands connected to idealized corporeal transformation may be concretized, reenacted and renegotiated. Second, the monstrous body here functions simultaneously as an embodied narrative device and a medium. Participants compare the emotional and physical experience of LARPing and zombie walking to that of consuming popular cultural texts in horror or thriller films and television. However, an aspect of zombie walks and LARPs is the concrete physical transformation of those who participate. Furthermore, the use of masks, clothing and jewelry all add tactile dimensions to (or enhance these dimensions in) an embodied experience of a story-world of monsters.